Itineraires Therapeutiques Pluriels Et Recours Tardif Des Malades De L’ulcere De Buruli Dans Les Centres De Prise En Charge Dans Le District Sanitaire De Yamoussoukro (Côte d’Ivoire) - Abel, Adjet A.; Lucien, Adou D.; Konan, Danièle O. (European Scientific Journal, ESJ, 2016)
Buruli ulcer is an infectious disease caused by Mycobacterium ulcerans. It begins with a lump, swelling, skin plate and progresses to severe ulceration and disabling sequelae . For over a decade, it is a real public health problem in Côte d’Ivoire. The institutions responsible for the fight against this disease advocate for patients in endemic areas early case detection and immediate recourse to specialized care centers. Despite this recommendation, the therapeutic itinerary of patients is multimodal. This study aims to analyze the therapeutic itinerary plural sick of Buruli ulcer and to determine the factors that justify the paradoxes and contradictions between state recommendations and behaviors of patients. It took place in three support centers in the health district of yamoussoukro. In a qualitative approach, with observation checklists, interview guides, this study was conducted with 50 patients, 18 healers in the care center and 4 traditional healers. Patients rely successively, alternatively or additionally to the African medicine and care center. Traditional medicine is the first therapeutic choice for most patients. The proximity of traditional healer, cultural beliefs and representations related to the disease, the constraints of hospitalization, ignorance of the disease make account plural therapeutic itineraries sick of Buruli ulcer.The patients do not adhere to early detection and immediate access to health care centers. Free medical care for Buruli ulcer is fraught with difficulties because of patient behaviors. The hospital management does not consider the social environment of patients and the relationship between the disease and culture that influence the therapeutic itinerary of patients.